PENINGKATAN DAYA BERPIKIR KRITIS DAN KEMAMPUAN LITERASI MAHASISWA TERHADAP KONDISI LINGKUNGAN KOTA BONTANG SEBAGAI KOTA INDUSTRI MELALUI PERKULIAHAN BAHASA INDONESIA - Irianto; Dzulkadvid, Zaldy (Manajemen Pendidikan Program Doktor, 2024)
By critically thinking, individuals are capable of analyzing anything around them. This can occur when an individual has applied critical literacy in their life. Literacy also impacts the environment, which can be implemented through knowledge, skills, attitudes, and behaviors. If students, especially those from Bontang City, can think critically and apply environmental literacy, then the ecological conditions of Bontang City will improve. This research aims to describe the extent of the influence of critical thinking and ecological literacy abilities of Bontang City students on the environmental conditions of Bontang City through Indonesian language lectures. This research was conducted using a qualitative method in the form of library research that uses books and other literature as objects. The results of this research indicate the extent of the influence of students on the environmental conditions of Bontang City through critical thinking and literacy abilities. If students' critical thinking and ecological literacy abilities are good, then the environmental conditions will be preserved.